SOSIALISASI SERIAL ANIMASI TENTANG PENGENALAN AJARAN BUDI PEKERTI JAWA DENGAN PENYAJIAN BERBAHASA JAWA - Exwan Andriyan Verrysaputro (Universitas Pahlawan Tuanku Tambusai, 2023)
The aims of this community service activity entitled Socialization of the animated series about introducing Javanese morals with the presentation of Javanese is to provide exposure to teachers throughout the Surakarta Residency in using the Javanese animated series as a tool for teaching Javanese and instilling moral values. character. This community service is carried out through the preparation stage and the implementation stage. Based on this socialization activity, the Javanese animation series can be used as a media aid in learning Javanese by children according to elementary school age. The animated series can also be used as a medium to help teachers to facilitate the inculcation of ethical or character values ??in students. So it can be concluded that this socialization activity is beneficial for teachers throughout the Surakarta Residency. Keywords: Outreach, animated series, teachers, students